Association between body mass index and short-term mortality in patients with intra-abdominal infections: a retrospective, single-centre cohort study using the Medical Information Mart for Intensive Care database - Chang Liu; Yingmu Tong; Sinan Liu; Kaibo Yang; Jingyao Zhang (BMJ Open)
Objectives This study aimed to determine the relationship between the body mass index (BMI) and short-term mortality of patients with intra-abdominal infection (IAI) using the Medical Information Mart for Intensive Care (MIMIC-III) database.Design Retrospective cohort study.Setting Adult intensive care units (ICUs) at a tertiary hospital in the USA .Participants Adult IAI ICU patients from 2001 to 2012 in the MIMIC-III database.Interventions In univariate analysis, we compared the differences in the characteristics of patients in each BMI group. Cox regression models were used to evaluate the relationships between BMI and short-term prognosis.Primary and secondary outcome measures 90-day survival.Results In total, 1161 patients with IAI were included. There were 399 (34.4%) patients with a normal BMI (<25 kg/m2), 357 (30.8%) overweight patients (25–30 kg/m2) and 405 (34.9%) obese patients (>30 kg/m2) who tended to be younger (p<0.001) and had higher Sequential Organ Failure Assessment scores (p<0.05). The mortality of obese patients at 90 days was lower than that of patients with a normal BMI (20.74% vs 23.25%, p<0.05), but their length of stay in the ICU was higher (4.9 days vs 3.6 days, p<0.001); however, their rate of mechanical ventilation utilisation was higher (61.48% vs 56.86%, p<0.05). In the Cox regression model, we also confirmed that BMI was a protective factor in patients with IAIs, and the adjusted mortality rate of patients with a higher BMI was 0.97 times lower than that of patients with a lower BMI (p<0.001, HR=0.97, 95% CI 0.96 to 0.99).Conclusions IAI patients with an overweight or obese status might have lower 90-day mortality than patients with a normal BMI.